EDUCAÇÃO FÍSICA E EDUCAÇÃO ESPECIAL (REMUNOM, 2024)
Abstract: This article highlights the importance of special education in physical education. The role of the school is to include students with disabilities in the school environment and transform this educational moment into a joyful moment of interpersonal respect and solidarity. The role of the teacher is to ensure this meaningful inclusion. Identify the difficulties encountered for inclusion in the school environment, identify some of the barriers that need to be addressed, such as the accessibility necessary for inclusion in the school environment, and understand what actions can enable the inclusion of children with special needs in everyday school life. The role of the physical educator is to adapt students with disabilities to their world in the real classroom. Keywords: Student, Disabled, Accessibility, School, Inclusion.